2007
DOI: 10.1203/01.pdr.0000250208.09874.91
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Restriction Impairs Nephrogenesis in a Gender-Specific Manner in the Ovine Fetus

Abstract: Inadequate nutrition compromises fetal development and poses long-term health risks for the offspring, even without decreased birth weight. The present study sought to 1) establish the ontogeny of fetal renal glomerulus number (GN) in sheep and 2) evaluate the effects of 50% global nutrient restriction (NR) during early to midgestation on GN and the renin-angiotensin system in the fetal kidney. GN increased from 78 dG (68,560 Ϯ 3802) to 135 dG (586,118 Ϯ 25,792). NR increased combined kidney weight (29 Ϯ 0.6 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 42 publications
(57 reference statements)
2
46
1
Order By: Relevance
“…The attenuation of the endothelial response to acetylcholine induced by this model was, however, present in both male and female offspring. In keeping with the predominantly male hypertensive effects of prenatal insults on development, studies have found more impaired renal function in male than in female rat offspring (Woods et al 2005, Gilbert et al 2007, Reverte et al 2011. Focusing on studies where the sexes are compared directly within the same model, it has been suggested that an anatomical basis for impaired renal function can be seen in a direct reduction of the number of nephrons in male offspring (Woods et al 2005).…”
Section: Humanmentioning
confidence: 99%
“…The attenuation of the endothelial response to acetylcholine induced by this model was, however, present in both male and female offspring. In keeping with the predominantly male hypertensive effects of prenatal insults on development, studies have found more impaired renal function in male than in female rat offspring (Woods et al 2005, Gilbert et al 2007, Reverte et al 2011. Focusing on studies where the sexes are compared directly within the same model, it has been suggested that an anatomical basis for impaired renal function can be seen in a direct reduction of the number of nephrons in male offspring (Woods et al 2005).…”
Section: Humanmentioning
confidence: 99%
“…Both of these gene products play important roles in renal function and alterations in either could have developmental and/or functional effects in the kidney (Baserga et al, 2007b). Similarly, sex differences have also been reported in the ontogeny of gene expression in the renal RAS (Gilbert et al, 2007a). Similar to the kidney, the mammary gland undergoes discrete phases of development.…”
Section: Fetal Developmentmentioning
confidence: 67%
“…In addition, only a subset of these studies has been evaluated for sex differences. Previous work has shown male sheep and baboon fetuses are more susceptible to the effects of poor maternal nutrition (Gilbert et al, 2005a;Gilbert et al, 2006a;Gilbert et al, 2007a). Studies in sheep have shown global caloric restriction impairs nephrogenesis and alters intrarenal immunoreactive AT 1 , AT 2 and renin expression in gestational age and gender specific ways (Gilbert et al, 2007a).…”
Section: Models Of Nutrient Restrictionmentioning
confidence: 99%
See 2 more Smart Citations